Caring Behavior Coding Scheme based on Swanson’s Theory of Caring – development and testing among undergraduate nursing students - Mårtensson, Sophie; Hodges, Eric A.; Knutsson, Susanne; Hjelm, Carina; Broström, Anders; Swanson, Kristen M.; Björk, Maria (Scandinavian journal of caring sciences, 2021)
Rationale To maintain patients’ dignity and well‐being and alleviate suffering, it is essential that healthcare providers engage in caring behaviours. Yet, every year patient boards receive an increasing number of complaints from patients and significant others regarding healthcare providers’ non‐caring behaviours. Defining and measuring both verbal and nonverbal caring and non‐caring behaviour in healthcare delivery is vital to address such complaints. However, no studies were found that incorporated a comprehensive theory of caring to code encounters between healthcare providers and patients. Aim The aim was to develop and test a Caring Behavior Coding Scheme based on Swanson’s Theory of Caring. Method An instrument development process was used for behavioural coding including observational data from thirty‐eight video recordings collected in an undergraduate nursing course at a Swedish University. The observational data involved interactions between undergraduate nursing students and a standardised patient. Result The Caring Behavior Coding Scheme (the CBCS), contains seventeen verbal and eight nonverbal behavioural codes, categorised as caring and non‐caring in accordance with Swanson’s Theory of Caring. Content and face validity were assessed. Timed‐event sequential continuous coding was performed in INTERACT software. The coder achieved excellent agreement with the developed gold standard (k = 0.87) and excellent mean inter‐rater reliability (k = 0.82). All domains in Swanson’s Theory of Caring were observed and coded in the interaction. Discussion/Conclusion The CBCS is a theory‐based instrument that contributes to research on healthcare providers’ behavioural encounters. It uses verbal and nonverbal caring and non‐caring behavioural codes to assess the alignment of both the theory and practice of caring. The CBCS can contribute to both development and measurement of interventions focused on improving healthcare providers’ caring behaviour with the intended outcome of patient well‐being.